Facilitators and barriers to accessing reproductive health care for migrant beer promoters in Cambodia, Laos, Thailand and Vietnam: A mixed methods study - Webber, Gail; Spitzer, Denise; Somrongthong, Ratana; Dat, Truong Cong; Kounnavongsa, Somphone (Université d'Ottawa | University of Ottawa, 2012)
Background The purpose of the research was to assess access to sexual and reproductive health services for migrant women who work as beer promoters. This mixed methods research was conducted in Phnom Penh, Cambodia, Bangkok, Thailand, Vientiane, Laos, and Hanoi, Vietnam during 2010 to 2011. Methods Focus groups were held with beer promoters and separate focus groups or interviews with key informants to explore the factors affecting beer promoters’ access to health care institutions for reproductive health care. The findings of the focus groups were used to develop a survey for beer promoters. This survey was conducted in popular health institutions for these women in each of the four Asian cities. Results Several common themes were evident. Work demands prevented beer promoters from accessing health care. Institutional factors affecting care included cost, location, environmental factors (e.g. waiting times, cleanliness and confidentiality) and service factors (e.g. staff attitudes, clinic hours, and availability of medications). Personal factors affecting access were shyness and fear, lack of knowledge, and support from family and friends. The survey of the beer promoters confirmed that cost, location and both environmental and service factors impact on access to health care services for beer promoters. Many beer promoters are sexually active, and a significant proportion of those surveyed rely on sex work to supplement their income. Many also drink with their clients. Despite a few differences amongst the surveyed population, the findings were remarkably similar across the four research sites. Conclusions Recommendations from the research include the provision of evening and weekend clinic hours to facilitate access, free or low cost clinics, and health insurance through employer or government plans which are easy to access for migrants. Other improvements that would facilitate the access of beer promoters to these services include increased funding to hire more staff (reducing waiting times) and to stock more needed medications, mobile clinics to come to the workplace or free transportation for beer promoters to the clinics, improved training to reduce health care provider stigma against beer promoters, and public education about the importance of reproductive health care, including preventative services.
Keywords: Beer promoters; Migrants; Sexual health; Reproductive health; Access to health services; Southeast Asia; Cambodia; Laos; Thailand; Vietnam